Value of government data - Humphry, Donald P. (Government procedures and operations., 2015)
The term ""government data"" includes diverse categories of government information products, such as information published by government agencies for statistical purposes; information in government administrative records on individuals and businesses; and physical measurements about natural phenomena recorded by government agencies. This book discusses the value of government data and provides a U.S. open data action plan as well as the open data policy.